2015
DOI: 10.1002/hast.491
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Thinking about Trustworthy Research into the Genetics of Intelligence

Abstract: The advent of new technologies has rekindled some hopes that it will be possible to identify genetic variants that will help to explain why individuals are different with respect to complex traits. At least one leader in the development of “whole genome sequencing”—the Chinese company BGI—has been quite public about its commitment to using the technique to investigate the genetics of intelligence in general and high intelligence in particular. Because one needs large samples to detect the small effects associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Due to its uniquely sensitive role in discourses regarding social inequality and individual differences, the field of genetics must avoid the repetition of previous mistakes by responsibly tempering claims as they pertain to education. In particular, research needs be attentive to the structural realities that underlie many observed educational differences among groups (Callier & Bonham, 2015; Parens & Appelbaum, 2015): findings should be grounded in the appropriate contexts, and interpretations that acknowledge these realities should be favored.…”
Section: Specific Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its uniquely sensitive role in discourses regarding social inequality and individual differences, the field of genetics must avoid the repetition of previous mistakes by responsibly tempering claims as they pertain to education. In particular, research needs be attentive to the structural realities that underlie many observed educational differences among groups (Callier & Bonham, 2015; Parens & Appelbaum, 2015): findings should be grounded in the appropriate contexts, and interpretations that acknowledge these realities should be favored.…”
Section: Specific Recommendationsmentioning
confidence: 99%
“…Their papers, especially their discovery work on the genetics of educational attainment (Okbay et al, 2016; Rietveld et al, 2013), are all accompanied by carefully worded online FAQs that offer context and clarity for interpreting their findings. This practice has been framed as “the best example of prophylaxis against hyperbole” (Parens & Appelbaum, 2015). They give clear guidance against overly simplistic interpretations of their findings: “Did you find ‘the gene’ for cognitive performance?…”
Section: Specific Recommendationsmentioning
confidence: 99%
“…Due to its uniquely sensitive role in discourses regarding social inequality and individual differences, those in the field of genetics must help to avoid the repetition of previous mistakes by responsibly tempering claims as they pertain to education. In particular, research needs be attentive to the structural realities that underlie many observed educational differences between groups (Callier & Bonham, 2015;Parens & Appelbaum, 2015); findings should be grounded in the appropriate contexts and interpretations that acknowledge these realities should be favored.…”
Section: A Refrain From Overly Broad Claimsmentioning
confidence: 99%
“…Their papers, especially their discovery work on the genetics of educational attainment (Okbay et al, 2016;Rietveld et al, 2013), are all accompanied by carefully worded online "FAQs" which are meant to offer context and clarity for interpreting their findings. This practice has been framed as "the best example of prophylaxis against hyperbole" (Parens & Appelbaum, 2015). They give clear guidance against overly simplistic interpretations of their findings: "Did you find 'the gene' for cognitive performance?…”
Section: A Refrain From Overly Broad Claimsmentioning
confidence: 99%